Pengetahuan Dan Pengalaman Kepala Keluarga Berhubungan Dengan Kesiapsiagaan Bencana Gempa Bumi - Ningsih, Dwi Putri Sulistiya; Effendi, Effendi; Rahmawati, Ida; Khanifah, Yani (Universitas Tribhuwana Tunggadewi, 2023)
Large-scale disasters such as earthquakes, tsunamis, and floods can occur in the province of Bengkulu. The National Disaster Management Agency documented earthquake disasters of high magnitude over ten years between 2010 and 2020, with impacts ranging from casualties to infrastructure damage. To reduce the disasters' impact, community preparedness is needed. This research aims to understand the relationship between knowledge and experience of disasters with the head of the family preparedness in the face of the danger of earthquakes in the Gulf of Sepang District, Bengkulu City. The descriptive-analytical research design with a cross-sectional approach was used. The study was conducted in May-July 2022 with a population of 899 household leaders in the Gulf of Sepang District, Bengkulu City. A large sample of 90 household leaders was selected using proportional sampling techniques. The univariate and bivariate data were analyzed using descriptive and Chi-square statistics. The results showed a significant relationship between knowledge and preparedness (p-value = 0,001) with a strong coefficient contingency score (C = 0,653). There was a significant relationship between household leaders' experience and readiness (p-value = 0.001) with a strong coefficient contingency score (C = 0,603). Increasing the role of community leaders in developing community-based disaster management initiatives to reduce the impact of disasters is recommended.